PREVALENCE AND PATTERN OF CONGENITAL HEART DISEASE IN HAZARA - BURKI, MUMTAZ KHAN; BABAR, GHUFRAN SAEED (Journal of Ayub Medical College Abbottabad, 2001)
Background: The incidence and particularly the pattern of congenital heart disease may vary in different geographical locations, but the extent to which such reported variations are attributable to differences in genetic predisposition, environmental factors, or in study methodology and diagnostic precision remains uncertain. There is. therefore, a continuing need for studies on various aspects of congenital heart disease, in different communities and races. Methods: This study was done on 188 consecutive cardiac patients reporting at Ayub Teaching Hospital, Abbottabad, Pakistan from June 1998 to June 2000. Results: 114 of 188 cardiac patients studied had congenital heart disease. Both sexes were equally affected. Ventricular septal defects were the most common lesions (relative frequency 61.4%), followed by Tetrology of Fallots, ASD and PDA with a relative frequency of 8.77%. The detection rate under one month was 28.07% and at one year 75.43%. Conclusion: There is therefore, a need for increased awareness, especially among primary health and other front line doctors for earlier case detection.